2020
DOI: 10.2147/idr.s203454
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Vaccine Against Group B <em>Streptococcus</em>: Recent Advances</p>

Abstract: Group B streptococcus (GBS) causes a high burden of neonatal and infant disease globally. Implementing a vaccine for pregnant women is a promising strategy to prevent neonatal and infant GBS disease and has been identified as a priority by the World Health Organisation (WHO). GBS serotype-specific polysaccharideprotein conjugate vaccines are at advanced stages of development, but a large number of participants would be required to undertake Phase III clinical efficacy trials. Efforts are therefore currently fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 105 publications
1
63
0
3
Order By: Relevance
“…Concerns have arisen as to the possible negative impact of large-scale prevention, as IAP may promote the emergence of antibiotic resistance, and early exposure to antibiotics can disrupt the development of the intestinal microbiome, with consequences in adulthood [ 6 ]. Finally, IAP has no impact on LOD, stillbirths and prematurity due to GBS, as well as a limited impact on disease in pregnant women [ 7 ]. Further strategies are urgently required to decrease GBS-associated morbidity and mortality.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns have arisen as to the possible negative impact of large-scale prevention, as IAP may promote the emergence of antibiotic resistance, and early exposure to antibiotics can disrupt the development of the intestinal microbiome, with consequences in adulthood [ 6 ]. Finally, IAP has no impact on LOD, stillbirths and prematurity due to GBS, as well as a limited impact on disease in pregnant women [ 7 ]. Further strategies are urgently required to decrease GBS-associated morbidity and mortality.…”
Section: Main Textmentioning
confidence: 99%
“…Although previous studies have shown an association between serotype-specific maternal IgG titers and reduction of neonatal disease risk, no study has been able to establish with certainty a protective antibody threshold value, due to different assays for determining antibody titers or inability to compare and pool the results of different studies [ 12 ]. Vaccines have been tested against serotype-specific capsular polysaccharide and against surface proteins that are expressed in different serotypes and could then protect against specific serotypes [ 7 , 12 ].…”
Section: Main Textmentioning
confidence: 99%
“…Currently, GBS vaccines are being developed as a new strategy to prevent GBS disease in neonates and infants. A suitable vaccine against GBS given to pregnant women could provide effective prophylaxis against invasive GBS diseases that cannot be prevented with IAP or where IAP is not feasible or is incomplete (Carreras-Abad et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While a rare cause of renal abscesses, primary prevention of invasive GBS infections may be on the horizon. After a promising phase I/II clinical trial, GBS conjugate vaccination in high-risk adults may be possible in the near future [ 16 , 17 ]. Given the increasing incidence of GBS invasive infections, this case presents a timely narrative of the potential benefit of a GBS vaccine for females of child-bearing age.…”
Section: Discussionmentioning
confidence: 99%